Kong Frederik den Andens Begravelse i Roskilde Domkirke d. 5. Juni 1588 - Hiort-Lorenzen, H.R. (Historisk Årbog for Roskilde Amt, 2019)
Kong Frederik den Andens Begravelse i Roskilde Domkirke d. 5. Juni 1588